2021
DOI: 10.1038/s41699-020-00194-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of device asymmetries and Schottky barriers on the helicity-dependent photoresponse of 2D phototransistors

Abstract: Circular photocurrents (CPC), namely circular photogalvanic (CPGE) and photon drag effects, have recently been reported both in monolayer and multilayer transition metal dichalcogenide (TMD) phototransistors. However, the underlying physics for the emergence of these effects are not yet fully understood. In particular, the emergence of CPGE is not compatible with the D3h crystal symmetry of two-dimensional TMDs, and should only be possible if the symmetry of the electronic states is reduced by influences such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Because of the broken inversion symmetry of a material, the illumination of CP light onto the material results in a helicity-dependent photocurrent, which is called CPGE (34)(35)(36)(37)(38)(39)(40)(41). In our polarimeter, the presence of anisotropic electric fields near the metal-BP contacts (originating from the Schottky barriers) will reduce the symmetry of the unit and result in a net CP photocurrent (42)(43)(44). In Fig.…”
Section: Self-driven Polarization Analysismentioning
confidence: 99%
“…Because of the broken inversion symmetry of a material, the illumination of CP light onto the material results in a helicity-dependent photocurrent, which is called CPGE (34)(35)(36)(37)(38)(39)(40)(41). In our polarimeter, the presence of anisotropic electric fields near the metal-BP contacts (originating from the Schottky barriers) will reduce the symmetry of the unit and result in a net CP photocurrent (42)(43)(44). In Fig.…”
Section: Self-driven Polarization Analysismentioning
confidence: 99%
“…Therefore, it is crucial to characterize the valley-coupled photocurrent at room temperature. Recently, it has been reported that the surface symmetry breaking and charge transfer in the TMD-based heterostructure could help to enhance the photoelectric response in TMDs, , which is expected to provide a feasible way to detect the valley photocurrent in TMDs at room temperature.…”
mentioning
confidence: 99%